Endoscopic vs. microscopic stapes surgery: An anatomical feasibility study - Blijleven, Esther E.; Willemsen, Koen; Bleys, Ronald L. A. W.; Stokroos, Robert J.; Wegner, Inge; Thomeer, Henricus G. X. M. (Frontiers in Surgery, 2022)
Objectives: To investigate the feasibility of the endoscopic approach versus microscopic approach during stapes surgery, focusing on the visualization of the important anatomical structures of the middle ear, the volume of the resected scutum and chorda tympani (CT) injury. Methods: Fresh frozen human cadaveric heads underwent two stapes surgeries using an operating microscope on one ear and an endoscope on the other ear. The surgeon documented the visualization of critical landmarks, as well as exposure and injury of the CT. The volume of resected scutum was evaluated using cone beam computed tomography scanning and three-dimensional imaging. Results: We performed endoscopic stapes surgery in 10 ears and microscopic stapes surgery in 11 ears. A stapes prosthesis was placed in all ears. The volume of bony scutum resection was significantly lower in the endoscopic group (median = 2.20 mm3, IQR = 4.17) than in the microscopic group (median 13.25 mm3, IQR = 8.71). No scutum was removed in two endoscopic ears, while scutum was removed in all microscopic ears. The endoscopic and microscopic group had similar CT injury. Conclusions: This study showed that the endoscopic stapes surgery procedure is feasible and might be less invasive than microscopic stapes surgery. Future clinical prospective and functional studies will be needed to support our findings.